2017
DOI: 10.21010/ajtcam.v14i5.21
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anti-Mycobacterial, Anti-Oxidative and Anti-Proliferative Activities of Rubia Cordifolia Ethanolic Leaf Extract Sub-Fractions in Human Lymphocytes and Neutrophils

Abstract: Background. Rubia cordifolia has been used to treat various diseases and exhibits antimicrobial, anti-inflammatory, analgesic and antidiarrheal activities. The plant has not been investigated for its anti-mycobacterial activity against virulent tuberculosis strains as well as cytotoxic and anti-oxidant activities in mononuclear cells and neutrophils. Methods. Ethanolic and dichloromethane leaf extract fractions of Rubia cordifolia (0.2-125µg/ml) were screened for anti-mycobacterial activity using a fluorescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Methanolic extracts of Rubia cordifolia equally exhibited moderately high anti-mycobacterial activity against all M. tuberculosis strains used. Similar or higher activity was reported by Makgatho et al, in a study carried out in South Africa to evaluate R. cordifolia anti-mycobacterial activity [25]. Crude 80% etha-nolic and methanolic extracts of both plant species had their inhibitory concentrations ranging as low as 23 μg/mL to 750 μg/ml.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Methanolic extracts of Rubia cordifolia equally exhibited moderately high anti-mycobacterial activity against all M. tuberculosis strains used. Similar or higher activity was reported by Makgatho et al, in a study carried out in South Africa to evaluate R. cordifolia anti-mycobacterial activity [25]. Crude 80% etha-nolic and methanolic extracts of both plant species had their inhibitory concentrations ranging as low as 23 μg/mL to 750 μg/ml.…”
Section: Discussionsupporting
confidence: 82%
“…The antimycobacterial activity of standard drugs was superior to that of the crude plant extracts because the latter contains a mixture of bioactive constituents of which some might antagonize the effects of others. Isolation of active molecules increases the activity of these compounds as reported for Zanthoxylum leprieurii [21], Zanthoxylum capense [30] and R. cordifolia [25].…”
Section: Discussionmentioning
confidence: 69%
“…This nding was consistent with other standard anti-TB drugs studied against MDR strains. This is in tandem with other previous studies that indicated that extracts of Z. leprieurii and R. cordifolia inhibited the growth of the MDR strain of Mycobacterium tuberculosis [4,20,22].…”
Section: Discussionsupporting
confidence: 90%